Spillovers Reconsidered: Analysing Economic Welfare under complementarities in R&D - Georg von Graevenitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
We analyse economic welfare in R&D intensive industries under varying assumptions on the spillover process. The focus lies on spillover processes with complementary R&D investments such as those modelling absorptive capacity. There spillovers give rise to both negative and positive externalities. We show that the rationale for public policy intervention is strengthened where spillovers also have positive effects. This conclusion is based on the supermodularity of the spillover process and the investment game. We characterise a large class of spillover processes with similar implications for public policy. We show that results of much empirical work on absorptive capacity extend to this class of models.
urn:nbn:de:bvb:19-epub-13519-6
Keywords: L13; O31; 330; spillovers; complementarity; absorptive capacity; supermodularity; oligopolistic R&D